Alkynyl triazenes enable divergent syntheses of 2-pyrones. Issue 26 (10th June 2021) - Tan, Jin-Fay; Bormann, Carl Thomas; Severin, Kay; Cramer, Nicolai
Abstract : Substituted 2-pyrones are accessed in a silver-catalyzed one-pot process between propiolic acids and 1-alkynyl triazenes. Subsequent diversifying replacement of the triazenyl unit under 1, 5-carbonyl transposition yields rare 2-fluoro pyrones. Abstract : The 2-pyrone motif occurs frequently in bioactive natural products and is appreciated as synthetic intermediates. However, only few methods allow for diversifying functional group modifications on this relevant heterocycle. The distinct properties of 1-alkynyl triazenes promote a smooth addition of propiolic acids across the triple bond. Addition of catalytic amounts of silver salt induces cyclization to 2-pyrones. Depending on the reaction temperature, either 6-triazenyl or 5-triazenyl 2-pyrones are selectively formed. The triazenyl unit is subsequently replaced by a variety of valuable groups in a one-pot process yielding for instance 2-fluoro pyrones. The substitution occurs with an intriguing 1, 5-carbonyl transposition. Moreover, the triazenyl group serves as traceless activating group for subsequent Diels–Alder cycloadditions and as a constituting unit for rare fused aminopyrazole pyrone heterocycles.